Ferrocene-based conjugated microporous polymer and its multiwalled carbon nanotube composite for direct photocatalytic benzene hydroxylation to phenol. Issue 53 (12th October 2021) - Zhu, Zhongpeng; Pan, Long; Liu, Zilu; Zhao, Jie; Tao, Zhiping; He, Yujian
Abstract : Ferrocene is used as a catalytically active site and building block to construct a new conjugated microporous polymer (CMP), named Fc-POP . Abstract : Ferrocene is used as a catalytically active site and building block to construct a new conjugated microporous polymer (CMP), named Fc-POP . A corresponding carbon nanotube composite (CNTs@Fc-POP ) with tubular structure was obtained through the π–π interaction between multi-walled carbon nanotubes (MWCNTs) and reactive molecules. This innovative modification method of carbon nanotubes provides a way to construct functionalized carbon materials. The two materials can achieve high conversion and selectivity of benzene hydroxylation to phenol under light irradiation using hydrogen peroxide (H2 O2 ) as an oxidant. Due to the synergistic effect between the carbon nanotubes and the ferrocene group, the incorporation of MWCNTs can improve the yield of phenol significantly. This work explores a new photocatalystic system and expands the related photocatalytic application of CNTs.